2017
DOI: 10.5935/0101-2800.20170022
|View full text |Cite|
|
Sign up to set email alerts
|

Acute effects of intradialytic aerobic exercise on solute removal, blood gases and oxidative stress in patients with chronic kidney disease

Abstract: The acute intradialytic aerobic exercise increased phosphorus serum concentration and decreased total antioxidant capacity, reversing hypoxemia resulting from hemodialysis. The intradialytic exercise did not change the blood acid-base balance and the removal of solutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 0 publications
0
35
1
13
Order By: Relevance
“…Five of seven studies showed a statistically significant result or a large effect size for increased potassium clearance and/or reduced serum concentrations with intradialytic exercise.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Five of seven studies showed a statistically significant result or a large effect size for increased potassium clearance and/or reduced serum concentrations with intradialytic exercise.…”
Section: Resultsmentioning
confidence: 95%
“…Seven of the acute studies utilized a within‐subject crossover design, with six of the seven randomizing the treatment order. One acute study implemented a randomized controlled design . Four of the intervention studies performed a randomized controlled trial, one study utilized a within subject crossover design, and two studies observed pre and post changes in an intervention group without a control comparison arm (1 group intervention) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12]18 Intradialytic exercise increases solutes removal by increasing cardiac output, which, combined with higher metabolic need for the exercising muscle, leads to muscle vasodilation. [5][6][7][8][9][10][11][12]18 Intradialytic exercise increases solutes removal by increasing cardiac output, which, combined with higher metabolic need for the exercising muscle, leads to muscle vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…There has already been some evidence that intradialytic exercise increases the amounts of phosphorus eliminated in dialysate, [5][6][7][8][9] as well as Kt/V-urea, 10-12 a parameter of HD adequacy. There has already been some evidence that intradialytic exercise increases the amounts of phosphorus eliminated in dialysate, [5][6][7][8][9] as well as Kt/V-urea, 10-12 a parameter of HD adequacy.…”
Section: Introductionmentioning
confidence: 99%